2022
DOI: 10.3390/ijms23158259
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Diazaspiro Cores as Piperazine Bioisosteres in the Development of σ2 Receptor Ligands

Abstract: A series of σ2R compounds containing benzimidazolone and diazacycloalkane cores was synthesized and evaluated in radioligand binding assays. Replacing the piperazine moiety in a lead compound with diazaspiroalkanes and the fused octahydropyrrolo[3,4-b] pyrrole ring system resulted in a loss in affinity for the σ2R. On the other hand, the bridged 2,5-diazabicyclo[2.2.1]heptane, 1,4-diazepine, and a 3-aminoazetidine analog possessed nanomolar affinities for the σ2R. Computational chemistry studies were also cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…In molecular docking studies, the receptor−ligand docking scores of compounds 1−4, 7, and 12 with the σ 2 receptor crystal are in good agreement with their affinity for the σ 2 receptor. Similar to the binding mode of other benzimidazolone derivatives reported recently, 42 a salt bridge with Asp29, hydrogen bond interactions with Asp29 and Tyr150, and π interactions with Tyr150 and Tyr50 have also been observed in the σ 2 receptor-binding site of compounds 1 and 2. Moreover, Asp56, Glu73, and Gln77 appear to play important roles for the binding of the σ 2 receptor to compounds reported here based on the mode analysis of molecular docking, consistent with the crucial amino acid residues identified initially.…”
Section: ■ Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In molecular docking studies, the receptor−ligand docking scores of compounds 1−4, 7, and 12 with the σ 2 receptor crystal are in good agreement with their affinity for the σ 2 receptor. Similar to the binding mode of other benzimidazolone derivatives reported recently, 42 a salt bridge with Asp29, hydrogen bond interactions with Asp29 and Tyr150, and π interactions with Tyr150 and Tyr50 have also been observed in the σ 2 receptor-binding site of compounds 1 and 2. Moreover, Asp56, Glu73, and Gln77 appear to play important roles for the binding of the σ 2 receptor to compounds reported here based on the mode analysis of molecular docking, consistent with the crucial amino acid residues identified initially.…”
Section: ■ Discussionsupporting
confidence: 84%
“…: 173.2−176.1 °C. 1 1-(Benzyloxy)-4-iodobenzene (42). To a solution of compound 40 (1300 mg, 4 mmol) in DMF (20 mL) were added K 2 CO 3 (5545 mg, 25 mmol) and benzyl bromide (5131 mg, 30 mmol).…”
Section: -(4-(6-(2-fluoroethoxy)-1h-benzo[d]mentioning
confidence: 99%
“…Both molecular docking and MDS studies have been used to identify the important interactions between a small molecule and key amino acid residues in a protein that contribute to the high-affinity binding of the ligand for the protein. These methods also reveal the active conformations of the ligands that are important in the binding of flexible ligands to the target protein [ 104 , 107 , 108 , 109 , 110 ]. This approach has been utilized in the development of ligands for G protein-coupled receptors, such as the dopamine D2 and D3 receptors, by investigating the ligand binding profiles in two different binding sites in the receptor, the OBS and SBS.…”
Section: Hit Compound Optimizationmentioning
confidence: 99%
“…The objective of this study was to conduct an SAR study investigating the replacement of the piperazine moiety of the lead compound, BF2846, with bridged or spirocyclic diamines. We previously demonstrated that this substitution was successful in developing selective ligands for other protein targets, including the dopamine D3 receptor, sigma-2 receptor, or PARP-1 . We hypothesized that this isosteric replacement of the piperazine ring may improve the selectivity of this scaffold for α-syn versus Aβ fibrils.…”
Section: Discussionmentioning
confidence: 99%